Voting experiments: bandwagon voting or false-consensus effect? - Ivo Bischoff; Henrik Egbert (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
In an experiment designed to test for expressive voting, Tyran (JPubEc 2004) found a strong positive correlation between the participants' approval for a proposal to donate money for charity and their expected approval rate for fellow voters. This phenomenon can be due to bandwagon voting or a false consensus effect. The social science literature reports both effects for voting decisions. Replicating Tyran's experiment and adding new treatments, we provide evidence for a false consensus effect but find no support for bandwagon voting.
Keywords: C90; D72; 330; voting; experiments; bandwagon voting; false consensus effect